(untitled) (Bangladesh Journal of Neuroscience, 2015)
Sarcopenia is a syndrome characterized by progressive and generalized loss of skeletal muscle mass and strength with a risk of adverse outcomes such as physical disability, poor quality of life and death. With the onset of advancing age, muscle tissue is gradually lost, resulting in diminished mass and strength, a condition referred to as sarcopenia. The sequelae of sarcopenia often contribute to frailty, decreased independence, and subsequently increased health care costs. This review article will introduce potential mechanisms that may contribute to sarcopenia, although no one mechanism has yet, and may not completely, define this process. Despite sarcopenia is an inevitable process of life, prevention and treatments are absolutely needed in order to improve the quality of life and quality adjusted life years. Adequate nutrition and structured exercises are essential components of treatment and prevention. However, even those individuals who maintain their fitness through exercise do not appear to be immune to sarcopenia. Bangladesh Journal of Neuroscience 2015; Vol. 31 (2): 110-115